Perbaikan Proses Bisnis Layanan Tes TOEFL Pada Unit Pengembangan Bahasa (UPB) Universitas Brawijaya Menggunakan Metode Business Process Improvement (BPI) - Febiko Ramadina; Nanang Yudi Setiawan; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Unit Pengembangan Bahasa (UPB) is an institution business unit of Universitas Brawijaya has a function in the field of the TOEFL Test. In carrying out the business process has several obstacles, like processes carried out manually and there are also online, making many activities with the same purpose repeated, services that are less than optimal, complicated activities make the time taken longer. Therefore, analysis and evaluation is needed to help and accelerate business processes in order to run more effectively and efficiently. This research begins with analysis business process primary and business process second of TOEFL test service, Failure Mode and Effect Analysis (FMEA) a method for analyzing the root causes and potential in business processes as a evaluation business process. Business Process Improvement (BPI) to get business process recommendations. Then there will be a simulation of validation and time analysis for current business processes (as is) and recommendations (to be), the results of current business process analysis will be compared with business process recommendations. from the 5 current sub-business processes and recommendations found the highest time effectiveness in the business process of the TOEFL test implementation to 72.32% and the lowest time effectiveness in the business process results and TOEFL test certificates up to 4.95%. So that business processes can be concluded. recommendations can improve performance better.